It's not time to make a change: Sovereign fragility and the corporate credit risk - Fabio Fornari; Andrea Zaghini (European Central Bank (ECB), 2022)
Relying on a perspective borrowed from monetary policy announcements and introducing an econometric twist in the traditional event study analysis, we document the existence of an "event risk transfer", namely a significant credit risk transmission from the sovereign to the corporate sector after a sovereign rating downgrade. We find that after the delivery of the downgrade, corporate CDS spreads rise by 36% per annum and there is a widespread contagion across countries, in particular among those which were most exposed to the sovereign debt crisis. This effect exists on top of the standard relation between sovereign and corporate credit risk.
Keywords: C21; G12; G14; 330; Credit Default Swaps; Credit Rating; Sovereign Risk Spillover